Wołyń - poszukiwania tożsamości wśród ludności = Volhynia - in search of the identity among the local population - Vaculík, Jaroslav (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The characteristic feature of Volhynia consisted in the fact that particular groups of people preserved their uniqueness, live separately, created their own settlements or independent center on the existing territory. Social, ethnic, cultural, religious and national differences remained strong throughout the entire period between the Wars.
Keywords: Wołyń; tożsamość; wieloetniczność; wielokulturowość; wieloreligijność; wielonarodowość